The Role of Extracurricular Educational Activities in Enhancing Social Adaptation among Youth in the Negev Region from the Perspective of Field Workers - Al-Kian, Jaber Abu (Journal of Posthumanism, 2025)
The current study aimed to explore the role of extracurricular educational activities in enhancing social adaptation among youth in the Negev region from the perspective of those working there. The study followed the descriptive survey methodology, and a questionnaire tool was developed, with its validity and reliability were verified. The questionnaire consisted of 32 items, consisted of five fields which are: environmental adaptation (included 5 items), social adaptation (included 6 items), cultural adaptation (included 5 items), structural adaptation (included 6 items), and educational adaptation (included 10 items). The questionnaire was converted to an electronic form. The study sample consisted of (105) employees. The findings showed that the role of extracurricular educational activities in enhancing social adaptation among youth in the Negev region, from the perspective of those working there, was high. Furthermore, the findings showed no statistically significant differences attributable to variables such as job title, gender, years of experience, and academic degree. The study suggested offering a variety of extracurricular activities such as recreation, social, cultural, and environmental areas. This would help community members to develop their social skills and discover their interests.